Liming by using CaCO3 for maintaining the quality of soil brackish water pond and the growth of seaweed Gracilaria sp. - Endang Arini (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
The intensive of shrimp culture in pond without applying of aquaculture management would be affected on acid soil doe to organic matter sources from the food and result of metabolic from the cultivar. Effort to maintenance soil quality can be occurred by using agriculture lime stone (CaCO3) and seaweed (Gracilaria sp) can be reared in the processes. The aims of the research were to know several doses of liming on the growth and the daily growth rate of Gracilaria sp. The research design applied was completely random design with four treatments and four repetitions. The following treatments were A (without liming), B (0,02 g/m2 ), C (0,03 g/m2) and D (0,04 g/m2 ).Data analyzed by using anova and Duncan’s test. The results of the research were indicate that liming application was highly significant (P>0,01) on the growth and daily growth rate. The dose of 0,04 g/m2 gave a highest result, that is 11,298 g for the growth and 1,141%/day for the daily growth rate. Key words : acid soil, liming, growth and Gracilaria sp.